Políticas públicas locales y desarrollo - Vargas, Braulio (2004)
This research offers a conceptual basis on public policies and their extension towards State policies, with an emphasis on policies to promote social and economic development in the context of decentralization. It reviews the evolution of public policies, from the welfare state approach to the modern approach of the promoter State, and then explains the process of designing and managing public policies. The article calls the attention to public policies as a way to transforming a situation of social dissatisfaction into a situation of social satisfaction.